2015
DOI: 10.4315/0362-028x.jfp-14-463
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Graphene Oxide on Intestinal Bacteria and Caco-2 Cells

Abstract: In recent years, novel nanomaterials have received much attention due to their great potential for applications in agriculture, food safety, and food packaging. Among them, graphene and graphene oxide (GO) are emerging as promising nanomaterials that may have a profound impact on food packaging. However, there are some concerns from consumers and the scientific community about the potential toxicity and biocompatibility of nanomaterials. In this study, we investigated the antibacterial properties of GO against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Moreover, treatments with nondigested GRMs, used as controls, further indicated neither significant decrease in cell viability, nor damage of cell membrane ( Figure S5b,c, Supporting Information), in line with previously reported data on the same cell type. [18,19] Therefore, lack of cytotoxicity in these cells after exposure to digested GRMs likely suggests no toxicity on intestinal barrier, as well.…”
Section: Cellular Uptake and Intracellular Localization Of Digested Grmsmentioning
confidence: 99%
“…Moreover, treatments with nondigested GRMs, used as controls, further indicated neither significant decrease in cell viability, nor damage of cell membrane ( Figure S5b,c, Supporting Information), in line with previously reported data on the same cell type. [18,19] Therefore, lack of cytotoxicity in these cells after exposure to digested GRMs likely suggests no toxicity on intestinal barrier, as well.…”
Section: Cellular Uptake and Intracellular Localization Of Digested Grmsmentioning
confidence: 99%
“…Although the toxicity of GO to organisms is unclear, some recent studies showed that GO caused cytotoxicity in some bacteria and cells (Combarros et al, 2016;Nguyen et al, 2015), while another recent study reported that purified GO did not have in-vitro cytotoxicity (Ali-Boucetta et al, 2013). Moreover, the environmental impact of GO on some organisms and the fate of inorganic substances can be significant (Mukherjee et al, 2016;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore it is an important point to obtain clear evidence that GO traces are not harmful upon casual ingestion. Only recently the impact of different GO on undifferentiated Caco-2 cells has been reported [19–21], revealing the formation of reactive oxygen species (ROS) induced by GO as well as a close GO-cell surface interaction. Nevertheless no acute toxicity of the applied GO for an exposure range of 5–80 µg GO/ml and an exposure time up to 48 h could be found [20].…”
Section: Introductionmentioning
confidence: 99%